Calibration method of rotation and displacement systematic errors for ship-borne mobile surveying systems. Issue 364 (2nd January 2019) - Lu, Xiushan; Feng, Chengkai; Ma, Yue; Yang, Fanlin; Shi, Bo; Su, Dianpeng
Abstract : Rotation and displacement errors between sensors and the Inertial Navigation System have significant effects on the accuracy of measured point clouds. In ship-borne mobile surveying systems, over and underwater targets are measured by a laser scanner and multibeam echo sounder, respectively. A simple calibration method and a universal calibration field are urgently needed to address both rotation errors and displacement problems for over and underwater sensors. First, a systematic error analytic function is established through the path that the geolocation expression of measured data is derived and substituted into the expression of known calibration planes. Then, the calibration expression that can calibrate both rotation errors and displacement is derived based on the least-squares criteria using a designed calibration pool. The calibrating results showed that for both over and underwater sensors, the accuracies of rotation errors and displacement estimation are better than 0.015° and 1.2 mm, respectively. After this calibration, the geolocation accuracy of measured points is better than 5 cm within a range of 30 m. The method can effectively calibrate systematic errors and serve as guidance to address the calibration problem for mobile surveying systems.